TEKS TUTUR DEWI GANGGA ANALISIS STRUKTUR, FUNGSI, DAN MAKNA - I Wayan, Rony Antara (Humanis; Volume 13. No.1. Oktober 2015)
This study discusses the oracle text Dewi Gangga Tutur with the analysis of the structure, function, and meaning. This analysis aims to reveal the structure of the building of the literary work as well as the functions and meanings contained therein. This research can provide guidance and reflection of life for humanity towards a harmonious life. The theory used in this study is the structural theory according to Ratna, Teeuw, and Nurgiyantoro. Methods and techniques used in this study were divided into three phases namely, (1) the stage of data collection method is used to read assisted with translation techniques, (2) the stage of data analysis used descriptive method and hermeneutics, (3) the stage of presentation of the results of the analysis used informal methods assisted with the deductive-inductive techniques.The results obtained from this study is srtuktur narrative consisting of: plot, character and characterization, setting, theme, and mandate. In addition, this study reveal the function of affirmation that define socio-cultural norms that exist at a particular time and a useful educational function for a way of life for the community. Meaning contained in the text of the Dewi Gangga Tutur is composed of: meaning pangruwatan or purification of the soul, meaning breeding, and the meaning of enlightenment.
Keywords: Tutur, Text, Structure